Temporal lobe epilepsy and focal cortical dysplasia in children: A tip to find the abnormality. (16th November 2016) - Bartolini, Luca; Whitehead, Matthew T.; Ho, Cheng‐Ying; Sepeta, Leigh N.; Oluigbo, Chima O.; Havens, Kathryn; Freilich, Emily R.; Schreiber, John M.; Gaillard, William D.
Summary: Objective: To demonstrate an association between magnetic resonance imaging (MRI) findings and pathologic characteristics in children who had surgery for medically refractory epilepsy due to focal cortical dysplasia (FCD). Methods: We retrospectively studied 110 children who had epilepsy surgery. Twenty‐seven patients with FCD were included. Thirteen had temporal lobe epilepsy (TLE) and 14 had extra‐temporal lobe epilepsy (ETLE). Three patients had associated mesial temporal sclerosis. Preoperative 3T MRIs interleaved with nine controls were blindly re‐reviewed and categorized according to signal alteration. Pathologic specimens were classified according to the 2011 International League Against Epilepsy (ILAE) classification and compared to MRI studies. Results: Rates of pathology subtypes differed between TLE and ETLE (χ 2 (3) = 8.57, p = 0.04). FCD type I was more frequent in TLE, whereas FCD type II was more frequent in ETLE. In the TLE group, nine patients had temporal tip abnormalities. They all exhibited gray–white matter blurring with decreased myelination and white matter hyperintense signal. Blurring involved the whole temporal tip, not just the area of dysplasia. These patients were less likely to demonstrate cortical thickening compared to those without temporal tip findings (χ 2 (1) = 9.55, p = 0.002). Three of them had FCD Ib, three had FCD IIa, two had FCD IIIa, and one had FCD IIb; MRI features could not entirely distinguish between FCD subtypes. TLE patients showed more pronounced findings than ETLE on MRI (χ 2 (1) = 11.95, p = 0.003, odds ratio [OR] 18.00). In all cases of FCD, isolated blurring was more likely to be associated with FCD II, whereas blurring with decreased myelination was seen with FCD I (χ 2 (6) = 13.07, p = 0.042). Significance: Our study described associations between MRI characteristics and pathology in children with FCD and offered a detailed analysis of temporal lobe tip abnormalities and FCD subtypes in children with TLE. These findings may contribute to the presurgical evaluation of patients with refractory epilepsy.